2001
DOI: 10.1080/028418501127346756
|View full text |Cite
|
Sign up to set email alerts
|

Safety of gadolinium contrast agent in hemodialysis patients

Abstract: Neither side effects nor blood changes were noted in any of the patients. Average excretory rates were 78.2%, 95.6%, 98.7% and 99.5% in the first to fourth hemodialysis sessions, respectively. These results suggest that Gd contrast agents can be used in hemodialysis patients if hemodialysis is carried out promptly after the examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
1
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(55 citation statements)
references
References 0 publications
2
51
1
1
Order By: Relevance
“…After three consecutive hemodialysis sessions over 6 days, 97% of the initial concentration of gadodiamide were eliminated [17]. In another study of 70 patients no side effects were noted [18]. This was also the case in the 6 patients in whom hemodialysis was performed 3 days after the contrast medium injection.…”
Section: Elimination Of Gadolinium-based Contrast Mediamentioning
confidence: 86%
See 1 more Smart Citation
“…After three consecutive hemodialysis sessions over 6 days, 97% of the initial concentration of gadodiamide were eliminated [17]. In another study of 70 patients no side effects were noted [18]. This was also the case in the 6 patients in whom hemodialysis was performed 3 days after the contrast medium injection.…”
Section: Elimination Of Gadolinium-based Contrast Mediamentioning
confidence: 86%
“…The extrarenal elimination of gadolinium is very small and less than 2% of the injected dose is excreted in the feces within 5 days of injection [17]. Good hemodialysability and safety of MRI gadolinium-based contrast agents have been reported [17,18]. After three consecutive hemodialysis sessions over 6 days, 97% of the initial concentration of gadodiamide were eliminated [17].…”
Section: Elimination Of Gadolinium-based Contrast Mediamentioning
confidence: 96%
“…The half-life of gadolinium in patients with normal kidney function is approximately 90 minutes, but in patients with advanced renal impairment, the elimination half-life can be prolonged to more than 30 hours [113]. Although, there is no evidence that hemodialysis immediately after gadolinium exposure lowers the risk or severity of NSF, studies have reported that gadolinium removal was up to 99% after three dialysis sessions [114][115][116]. Restoration of kidney function results in Gd excretion and detection in the urine, even if the contrast agent was administered up to three years prior to transplantation [54,117], suggesting that mobilization from tissue and bone deposits [115,118] can occur after transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, iron oxides are licensed as food coloring agents under the number E172, have been approved by the FDA for use in contact lenses (§ 73.3125), and they form the contrast-generating compound in the MRI contrast agent Lumirem® (ferumoxsil; Guerbet Groupe, France), which is approved for oral and rectal application at concentrations up to 175 mg Fe/l [9,19,20]. Thus, incorporation of iron oxides into the mesh material does not seem to pose any risks of side effects, such as might be present with other MR contrast agents, such as Gd-DTPA from which the toxic element gadolinium could potentially be washed out of the mesh during the long exposure times [21,22,23]. …”
Section: Discussionmentioning
confidence: 99%